Tirumala Tirupati Devasthanam: Sacred Heritage and Development Strategy - Gautam, Prakash (Journal of Tourism & Adventure, 2025)
Sacred heritage can refer to religious properties and places. It reflects and transmits ancient and cultural values. The Tirumala Tirupati Devasthanam (TTD) symbolises India’s religious heritage and Sanatana Dharma (the eternal order of Hinduism). The temples, sculptures, paintings, musical literature, dances, and other art forms that belong to the TTD are marked for prosperity and well-being. The TTD trust is located in Tirupati, Andhra Pradesh, India. It is one of the major religious trusts that focuses on social development perspectives. In this study, the author explored the cultural importance, governance, and social contribution of the TTD. A qualitative case study leveraging secondary data and interviews of the TTD was conducted to examine its activities for community development in the Tirumala and Tirupati areas. The results indicated that the trust’s income has increased owing to the excellent management and utilisation of information technology. Following the increase in its properties, the trust has started to invest capital into three major sectors: (i) employment opportunities, (ii) infrastructure and corporate social responsibility activities, and (iii) environmental protection. The TTD is a compelling example of sustainable management, and other religious trusts can also adopt its strategies.